Opportunities and challenges of implementing computational thinking through unplugged activities in physics learning - Ahmad Fauzi; Shofi Hikmatuz Zahroh (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2023)
Computational thinking is one of the universal competencies that students must master in facing the challenges of the 21st century. This study describes the opportunities and challenges of applying computational thinking through unplugged activities in physics learning, especially in senior high school. This research was involved with survey research and a cross-sectional survey design type. The respondents of this study were physics teachers in the city of Semarang and Surakarta. The number of respondents in this study was 43 people. Data were taken by using questionnaires and interview techniques. This study's result indicates opportunities for applying computational thinking through unplugged activities in physics learning. Most respondents welcomed the application of computational thinking through unplugged activities in physics learning. However, according to some teachers, several aspects might become obstacles to implementing computational thinking through unplugged activities, namely the difficulty of making algorithms and simulation.